From Conversation to Contract: The Notary's Role in Nineteenth-Century Montreal - Olson, Sherry; Poutanen, Mary Anne (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Famille; Notaires

Marriage, Proprety, and the Law in a Square Mile Family: The Case of Annie Stevenson Anderson vs David Morrice, 1884-1885 - Gossage, Peter; Moore, Lisa (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Femmes; Golden Square Mile; Mariage; Quartiers; Tribunaux

The National Federation of Labor Youth and the Candy Bar Kids: Radical Youth, Popular Protest, and the Red Scare in Postwar Canada - Guard, Julie (Labour / Le Travail, 2024)
Keywords: Communistes; Enfants; Grèves

Crossing Imperial Boundaries and Constructing Intimate Linkages: reading Soldiers' First World's War Letters - Kenny, Nicolas (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Guerre

Dans la rue. Une histoire du FRAPRU et des luttes pour le logement au Québec - Saillant, François (Écosociété, 2024)
Keywords: Groupes populaires; Logement

The Voice of the Child Cries Out Against You: The 1912 Montreal Child Welfare Exhibition in its North American and Transnational Contexts - Vanier, Marie-Hélène (Université Concordia, 2024)
Keywords: Enfants; Exposition; Mortalité

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

Les coûts de la vie : genre, citoyenneté et politique des prix à Montréal dans les années 1940 - Fahrni, Magda (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Alimentation; Femmes; Prix; Épicerie

Social Transformation in Notre Dame de Grâce over the Long Sixties - Kastner, Jeffrey (Université McGill, 2023)
Keywords: Centres d'acceuil

Lueur urbaine : réverbères, émotions et vie nocturne, années 1880 à 1910 - Kenny, Nicolas (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Rues; Électricité

Sur les pas d’Oscar et d’Oliver dans la Petite-Bourgogne. Première partie : Vie associative dans le quartier - Willis, John (Cap-aux-Diamants, 2023)
Keywords: Petite-Bourgogne; Quartiers

Le Comité d’Habitation de Montréal - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Groupes populaires; Logement

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

‘We have always been here’: Busking, urban space and economy of Montreal - Chatterjee, Piyusha (Université Concordia, 2022)

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

« Se soumettre de bon coeur à son mari »: le combat d'une femme face à l'autoritarisme marital - Lamonde, Yvan (Presses de l'Université Laval, 2022)
Keywords: Avocats; Doutre, Joseph; Femmes; Guibord, Joseph; Institut canadien; Mariage; Renaud, Marie-Zoé-Aimée; Trudel, François-Xavier-Anselme; Ultramontains

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

La Ligue ouvrière catholique et la naissance de la paroisse Saint-André-Apôtre (première partie) - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Famille; Jeunesse ouvrière catholique (JOC); Ligue ouvrière catholique; Logement; Quartiers

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Logement

Habiter le monde autrement: Sur quelques témoignages publiés dans Mainmise - Rondeau, Frédéric (Quebec Studies, 2022)
Keywords: Paysage

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

Le Montréal juif – (3e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

Faire chambre à part. Patients indigents et payants dans les hôpitaux généraux de Montréal en 1911 - Petitclerc, Martin; Rousseau, Yvan; Guérard, François (Canadian Historical Review, 2021)
Keywords: Hôpital Notre-Dame; Hôpitaux; Hôtel-Dieu; Royal Victoria Hospital

Going Together Like a Horse and Carriage: Rentier Marriages and Property Accumulation in Montréal, 1825-1903 - Sweeney, Robert C. H. (Histoire sociale / Social History, 2021)
Keywords: Famille; Logement; Mariage

Politique de l’amour dans La Vie en rose (1980-1987): discours et rhétorique de la désobéissance - Bergeron, Marie-Andrée (Recherches sociographiques, 2021)
Keywords: Femmes

L’amour au temps du tramway: le " romantisme pragmatique " de la journaliste Robertine Barry, alias Françoise (1863-1910) - Doucet, Sophie; Fortin, Jonathan (Recherches sociographiques, 2021)
Keywords: Barry, Robertine; Journalistes; Mariage; Patrie (La); Écrivains

Un triangle amoureux médiatique. Le célibataire célèbre, la lectrice amoureuse et le rédacteur entremetteur dans le magazine Radiomonde - Loranger, Caroline (Recherches sociographiques, 2021)
Keywords: Radio

La revue Mon Mariage: vendre du rêve (1948-1951) - Luneau, Marie-Pier; Warren, Jean-Philippe (Recherches sociographiques, 2021)
Keywords: Mariage

Le magazine féminin, " piège à mariage moderne " ou repaire de célibataires irréductibles? Le cas de La revue Moderne et des enquêtes de Luc Aubry dans les années 1920 - Rannaud, Adrien (Recherches sociographiques, 2021)
Keywords: Gleason, Anne-Marie (Madeleine); Journalistes; Mariage; Revue moderne (La)

The Goode House (The Westmount Historian, 2021)
Keywords: Conservation; Famille; Jardins; Patrimoine

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

Quand le temps s'arrête: une promenade dans le jardin de la maison Goode / Window to the Past: A Walk in the Garden of the Goode House - Adib, Danièle; Crépeau, Antoine (The Westmount Historian, 2021)
Keywords: Jardins

Enfin chez soi! - Archambault-Malouin, Diane; Beauchamp, Maurice; St-Marseille, Michel (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Coopérative d'habitation de Montréal; La Familiale; Logement; Sault-au-Récollet

Three Generations of Goode Family - Breslaw, Caroline (The Westmount Historian, 2021)
Keywords: Famille

History, Memory, and Struggle in Saint-Henri, Montreal - Burrill, Fred (Université Concordia, 2021)
Keywords: Saint-Henri; Travail

Le haut des côtes était la zone. Le nord-est d'Ahuntsic entre 1932 et 1944 - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Logement; Pauvreté; Quartiers

Montreal at War, 1914-1918 - Copp, Terry; Maavara, Alexander (The Canadian experience of war, 2021)
Keywords: Conscription; Guerre

Le discours sur la sexualité, l’alimentation et l’apparence corporelle des adolescentes québécoises durant la décennie 1980 : analyse du magazine Filles d’Aujourd’hui - Dumont-Lévesque, Catherine (Université de Sherbrooke, 2021)
Keywords: Enfants; Femmes

La presse gaie au Québec: vecteur d'une communauté - Giguère, Nicholas (Relire les revues québécoises: histoire, formes et pratiques (XXe-XXIe siècle), 2021)
Keywords: Fugues (revue)

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Famille; Logement; Quartiers; Rosemont

A Heuristic Archive: Jean-Paul Gill's Red Light Photographs - Guillaume, Philippe (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Archives; Patrimoine; Photographie; Quartiers; Saint-Laurent (quartier)

Gendered labour, immigration, and deindustrialization in Montreal's garment industry - Laframboise, Lauren (Université Concordia, 2021)
Keywords: Femmes; Grèves; Travail; Vêtements

Re-activations: Alain Chagnon’s Plateau-Mont-Royal in Translation - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Photographie; Plateau Mont-Royal; Quartiers

"Un petit pouvoir": The Compagnie des jeunes Canadiens, Animation Sociale, and Citizens’ Committees in Little Burgundy, Montreal, 1967-74 - Langford, Will (The Global Politics of Poverty in Canada. Development Programs and Democracy, 1964-1979, 2021)
Keywords: Groupes populaires; Pauvreté; Petite-Bourgogne; Quartiers

Joséphine Marchand et Raoul Dandurand. Amour, politique et féminisme - Lavigne, Marie; Stanton-Jean, Michèle (Biographie, 2021)
Keywords: Avocats; Féminisme; Journalistes; Marchand-Dandurand, Joséphine

Le Centre de services communautaires du Monastère (CSCM) - Loubert, Huguette (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
Keywords: Groupes populaires

Mary Travers Bolduc ou Madame Édouard Bolduc, pionnière de la chanson populaire au Québec - Melançon, Johanne (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Keywords: Bolduc, La; Chanson; Famille; Femmes

Gestion publique des personnes en situation de marginalité à Montréal. Quelques repères historiques - Parazelli, Michel; Bourbonnais, Mathieu (Itinérance et cohabitation urbaine. Regards, enjeux et stratégies d'action, 2021)
Keywords: Faubourgs; Itinérance; Pauvreté; Quartier des spectacles; Quartiers; Saint-Laurent (quartier)

Représentations sociospatiales des personnes en situation de marginalité dans les espaces publics (Montréal-Québec). Exploration des imaginaires sociaux dans la presse écrite francophone (1993-2018) - Parazelli, Michel; Carpentier, Marie-Ève (Itinérance et cohabitation urbaine. Regards, enjeux et stratégies d'action, 2021)
Keywords: Itinérance; Pauvreté

Enjeux politiques de la frontière entre salubrité et insalubrité dans l'habitation montréalaise des années 1930 - Racette, Jean-Christophe (Revue d'histoire de l'Amérique française, 2021)
Keywords: Crise; Logement; Pauvreté

Le marché Sainte-Anne au quotidien. Plus insalubre qu'il n'y paraît! - Roy, Christian (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

La représentation de la famille dans la peinture figurative nord-américaine durant la première moitié de la guerre froide (1945-1968) : les cas de Fairfield Porter, d'Alex Colville et de Jean Paul Lemieux - Scott, Christophe (Université du Québec à Montréal, 2021)
Keywords: Famille; Peinture

Le Montréal juif – (2e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2021)
Keywords: Juifs

Luttes pour le droit au logement sur le Plateau - Vallée, Bernard (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
Keywords: Crise; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Jobs, Homes, and the Right to Exist: Neighbourhood Activism in Deindustrializing Toronto and Montreal, 1963-1989 - Vickers, Simon (Université de Toronto, 2021)
Keywords: Quartiers; Travail

D’abord, prendre en mains son panier d’épicerie - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Keywords: Alimentation; Chaurès-Louard, Berthe; La Familiale; Logement; Épicerie

Le Plateau agricole (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
Keywords: Alimentation; Baron (côte à); Côtes; Institut des sourdes-muettes; Jardins; Meunerie; Plateau Mont-Royal

Women in Westmount (The Westmount Historian, 2020)
Keywords: Femmes; Peinture; Élections

Mémoires d'anciens "citoyens" de Boscoville. Enquête orale auprès de délinquants institutionnalisés entre 1954-1997 - Bienvenue, Louise (Question sociale et citoyenneté: la dimension politique des régulations sociales (XIXe-XXIe siècles), 2020)
Keywords: Boscoville; Délinquance; Enfants

Chronique d'une maisonnée d'Ahuntsic. La formation d'une institution au cours des années 1920 - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Keywords: Famille; Mariage

Grossières indécences: pratiques et identités homosexuelles à Montréal, 1880-1929 - Dagenais, Dominic (Études d'histoire du Québec / Studies on the history of Quebec, 2020)
Keywords: Clubs; Criminalité; Enfants; Police; Quartiers

Cohabitation, exploitation et nuisances à Montréal et à La Nouvelle-Orléans : les relations entre les populations urbaines et animales, 1840-1890 - Gagnon, Benjamin (Université du Québec à Trois-Rivières, 2020)
Keywords: Alimentation; Faune

Les " jeunes ", les " amazones ", les " célestes ": les figures de la panique morale sur les drogues à Montréal dans le journal La Patrie, entre 1921 et 1923 - Grenier, Amélie (Bulletin d'histoire politique, 2020)
Keywords: Chinois; Criminalité; Femmes; Patrie (La); Réformistes

Eau courante, toilettes à eau et dernières latrines à Montréal, 1856-1915 - Lauzon, Gilles (Revue d'histoire de l'Amérique française, 2020)
Keywords: Aqueduc; Égouts

Les droits et non la charité: les sans-emplois, les secours et la citoyenneté à Montréal pendant la Grande Dépression - Marsan, Benoît (Question sociale et citoyenneté: la dimension politique des régulations sociales (XIXe-XXIe siècles), 2020)
Keywords: Chômage; Crise; Groupes populaires; Travail

De vieilles filles à célibataires : une enquête d’histoire orale au Québec, 1940 à 1970 - McNeil, Françoise (Université de Sherbrooke, 2020)
Keywords: Femmes; Mariage

Sharing Montréal’s Village Gai - Podmore, Julie A. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Arrondissements; Quartiers; Ville-Marie (arrondissement)

Les Fourchettes de l'espoir. Un organisme au service de sa communauté depuis 19 ans - Reyes, Brunilda (Il était une fois... Montréal-Nord, 2020)
Keywords: Alimentation; Pauvreté

Le mouvement montréalais pour la fermeture de bonne heure des commerces. Genre, classe et régulation sociale du temps à l'époque libérale (1885-1909) - Rudy, Jarrett (Question sociale et citoyenneté: la dimension politique des régulations sociales (XIXe-XXIe siècles), 2020)
Keywords: Commerce de détail; Magasins; Marchands; Travail

Divvying up Space: Housing Segregation and National Identity in Early Twentieth-Century Montréal - Sweeny, Robert C. H. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Locataires; Logement; Quartiers

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

Le vice et la vertu: le Montréal 1940-1960 - Weintraub, William (Éditions Pierre Tisseyre, 2020)